Influence of Organizational Culture, Work Environment and Compensation on Job Satisfaction of Production Sector Employees: Pengaruh Budaya Organisasi, Lingkungan Kerja dan Kompensasi Terhadap Kepuasan Kerja Karyawan Bagian Produksi - Kurniawan, Tri Zanu Arief; Andriani, Dewi (Universitas Muhammadiyah Sidoarjo, 2022)
The Influence of Organizational Culture, Work Environment and Compensation on Job Satisfaction of Production Department Employees of PT. Putraduta Buanasentosa Sidoarjo.This thesis is not published. Management Study Program. Faculty of Business, Law & Social Sciences, University of Muhammadiyah Sidoarjo.This study aims to determine the effect of organizational culture, work environment and compensation on job satisfaction of Production Department employees of PT. Putraduta Buanasentosa.This research is a quantitative research with hypothesis testing. The sample used in this study were 73 employees of the production department at Putraduta Buanasentosa Sidoarjo. The analytical tool used in this study is multiple linear regression analysis using SPSS version 18 for windows. The primary data in this study were obtained from a questionnaire measured using a Likert scale which was tested for validity and reliability. The results of this study prove that organizational culture affects job satisfaction, work environment affects job satisfaction, compensation also affects job satisfaction, besides that organizational culture, work environment and compensation simultaneously influence job satisfaction,